1997
DOI: 10.1161/01.res.80.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Radicals Can Induce Preconditioning in Rabbit Hearts

Abstract: Indirect evidence suggests that oxygen radicals may contribute to ischemic preconditioning. We directly investigated whether exposure to oxygen radicals per se, in the absence of ischemia, could reproduce the beneficial effects of ischemic preconditioning on infarct size and on postischemic contractile dysfunction. In one branch of the study, isolated rabbit hearts underwent 30 minutes of total global ischemia and 45 minutes of reperfusion (n=6, control group). A second group, before ischemia/reperfusion, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(165 citation statements)
references
References 28 publications
5
156
0
2
Order By: Relevance
“…Preconditioning, a series of brief periods of ischemia and reperfusion, protects the myocardium from deleterious events associated with extended durations of ischemia and reperfusion (7)(8)(9). Cardioprotection afforded by preconditioning appears mediated, in part, by the production of oxygen radicals (35)(36)(37)(38)(39)(40) and is associated with reductions in Ca 2ϩ overload (7,(41)(42)(43) and free radical production (44) during extended periods of ischemia͞ reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Preconditioning, a series of brief periods of ischemia and reperfusion, protects the myocardium from deleterious events associated with extended durations of ischemia and reperfusion (7)(8)(9). Cardioprotection afforded by preconditioning appears mediated, in part, by the production of oxygen radicals (35)(36)(37)(38)(39)(40) and is associated with reductions in Ca 2ϩ overload (7,(41)(42)(43) and free radical production (44) during extended periods of ischemia͞ reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mitochondrial connexin-43 has also been implicated in ROS signaling although its role is not completely defined (14)(15)(16). A target of ROS in redox signaling is the PKC (possibly PKCe2); in fact hearts can be preconditioned by simply infusing free radicals into the coronary arteries and that protection can be blocked by a PKC antagonist (184). Indeed, it has been reported that ROS can activate PKC in vitro by reacting with thiol groups associated with the zinc finger region of the molecule (98).…”
Section: Interaction Between Redox Environment and Cardioprotective Pmentioning
confidence: 99%
“…At reperfusion, O 2 À and other ROS may strongly oxidize the cardiomyocytes already damaged by the ischemia, thus favoring cell death (1,2,53,116,183,184 in myocardial injury (10-12, 52, 135, 165). In particular, high ONOO À concentrations are considered to be highly cytotoxic (11,12,135,165).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that free radicals, which directly stimulate phospholipases in cells, also contribute to triggering preconditioning in the rabbit model. [191][192][193] Evidence also suggests that at least one tyrosine kinase that also may be involved in the mechanism of preconditioning exists downstream from PKC in the rabbit heart. 194 Similar findings were observed in a model of isolated rabbit cardiomyocytes developed by Armstrong et al 195,196 They assessed myocyte injury as the rate of development of osmotic fragility during prolonged ischemic pelleting of cells incubated under oil.…”
Section: Mechanism Of Preconditioningmentioning
confidence: 99%